Methoxyphenol derivatives as reversible inhibitors of myeloperoxidase as potential antiatherosclerotic agents - Jayaraj, Premkumar (Future Med Chem, 2019)
AIM: To evaluate new chemical entities, based on ferulic acid scaffolds, as reversible myeloperoxidase inhibitors (MPOI). METHODOLOGY & RESULTS: In silico docking studies are performed with MPO protein as a target for several ferulic acid analogs followed by multiple in vitro assays to validate this approach. Two lead compounds 2a and 3 are identified with optimum docking and IC(50) values: -7.95 kcal/mol, 0.9 μM and -8.35 kcal/mol, 8.5 μM, respectively. These MPOIs are able to inhibit oxidation of high-density lipoprotein and further promoted functionality of high-density lipoprotein. CONCLUSION: Lead analogs are potent MPOIs that exert specific effects on MPO-mediated oxidation as well as inflammatory pathways. It also acts as promoters of cholesterol efflux that sheds light on pharmacological approach in atherosclerosis treatment.